Dipolar Imidazoanthraquinoe Derivatives and Their Application in Solid State Devices: Synthesis, Characterization, and Applications of Dipolar Imidazoanthraquinoe Derivatives in Solid State Devices (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Imidazoanthraquinone based mixtures (AQ01-AQ07) were orchestrated and described. Mixtures AQ01 and AQ02 were chosen for additional investigations. Photo physical properties in different solvents recommended the polar idea of the ground state for AQ01 and AQ02. Fluorescence extinguishing tries different things with the normally utilized electron contributor poly-3-hexylthiophene found out the capability of these particles as electron acceptor for applications in sun based cell gadgets. Thickness practical hypothesis (DFT) gave knowledge on the dipolar nature, H-holding, and π−π collaboration in various kinds of supramolecular gatherings of AQ01 and AQ02. Computations anticipated that the π−π cooperation through antiparallel direction and Bonding with the OH•••OH association is vivaciously preferred in AQ01. Morphological investigations on thermally dissipated meager movies showed nano-gatherings like interconnected wires in AQ01 while blossom like irregular totals in AQ02. Charge transport properties of these atoms were assessed for AQ01AQ02 and their mixes with Poly(3-hexylthiophene-2,5-diyl) (P3HT). Opening portability in the AQ01-based gadget was observed to be of request of 10−4 cm 2V s. High opening versatility got for AQ01 relates well with the positive morphology saw in the slim film. Our outcomes show that the dipolar atom AQ01 can possibly be utilized as a non-fullerene based electron acceptor in BHJ sun powered cell gadgets.